2012
DOI: 10.7314/apjcp.2012.13.6.2519
|View full text |Cite
|
Sign up to set email alerts
|

Association of Genetic Polymorphisms at 1q22 but not 10q23 with Gastric Cancer in a Southern Chinese Population

Abstract: Objective: Data from a recent genome-wide association studiesy of gastric cancer (GC) and oesophageal squamous cell carcinoma in Chinese living in the Taihang Mountains of north-central China suggest that 1q22 and 10q23 are susceptibility-associated regions for GC. However, this has not been confirmed in southern Chinese populations. The aim of this study was to investigate whether these polymorphisms at 1q22 and 10q23 are associated with the risk of GC in a southern Chinese population. Methods: We selected se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
13
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 21 publications
2
13
0
Order By: Relevance
“…pylori serology in an independent case–control study of 335 GC cases and 334 controls in a Chinese population. The results were consistent with the association in the three GWASs [79] and other recently published independent replication studies in China [1921]. However, these studies all lacked data about H.…”
Section: Discussionsupporting
confidence: 90%
“…pylori serology in an independent case–control study of 335 GC cases and 334 controls in a Chinese population. The results were consistent with the association in the three GWASs [79] and other recently published independent replication studies in China [1921]. However, these studies all lacked data about H.…”
Section: Discussionsupporting
confidence: 90%
“…Whereas for gastric cancer and ESCC, no significant association was found in some researches. 23,24 The Genome-wide association studies conducted by Abnet et al found that the nonsynonymous variants rs3765524 of PLCE1 gene was associated with increased risk of ESCC. 14 Nevertheless the present study showed no association between rs3765524 and ESCC risk among Chinese Han population.…”
Section: Discussionmentioning
confidence: 98%
“…Risk allele A at the rs4072037 polymorphism has been reported to be associated with a decreased physiological function of MUC1 (33). Recently, many studies (4,(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)21) have reported the association between MUC1 rs4072037 polymorphism and GC susceptibility, but their findings were conflicting. And these studies may have had inadequate statistical power due to relatively small samples, clinical heterogeneity and different ethnic populations.…”
Section: Discussionmentioning
confidence: 99%